Розрахунок характеристик змішаної системи обслуговування з резервуванням каналів - Melikov, A. Z.; Velibekov, A. M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2008)
Algorithms for approximate calculation of the characteristics of mixed multichannel service system with two types of calls is proposed. In this system, impatient high priority calls are serviced on the basis of channel reservation scheme while low priority calls may be queued in either finite or infinite buffer. The results of numerical experiments are presented.